Strategi Komunikasi Publik Suku Dinas Komunikasi Informatika dan Statistik Jakarta Selatan dalam Membangun Citra Positif melalui Diseminasi Informasi - Najwa Amani Putri; Elpa Hermawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
In the midst of increasingly rapid and complex information flows in the digital era, the ability of government institutions to establish effective communication has become crucial in shaping a positive public image. This study aims to examine the public communication strategies implemented by the South Jakarta Department of Communication, Informatics, and Statistics in delivering information to the public in a transparent, accurate, and participatory manner. Employing a qualitative approach with a descriptive method, data were obtained through in-depth interviews, observation, and documentation. The findings reveal that the department actively utilizes social media and digital channels, fosters two-way communication, and crafts messages that are adaptive to public needs. Despite these efforts, challenges persist, such as limited human resources, disruptions in digital infrastructure, and the spread of disinformation that undermines public trust. This study underscores the importance of communication strategies that are not only technical but also ethical and humanistic, positioning the public as partners in dialogue. These findings are expected to contribute to strengthening the communication capacity of government institutions that are oriented toward service, transparency, and collaboration.